Development of Biodiversity Materials through Interactive Powerpoint in 10th Grade of Senior High School - Linda Pramita; Yetty hastiana; Rusdy A Siroj (BIODIK, 2019)
This study aims to produce teaching materials in the form of Interactive PowerPoints of biodiversity material. This research method is the development of Research and Development (R & D) using Tessmer development model with the stages of Self Evaluation, Exspert Reviews, One to One, Small Group and Field Test. Data collection were in the form of interviews and questionnaires. Subjects in this study were 11th grade of SMA Nurul Yaqin. The analysis of the results of the validation sheet and student questionnaire in this study was using quantitative and qualitative analysis techniques. Validation results are categorized as very feasible, the feasibility of Interactive Powerpoint teaching materials is drawn from media experts, 46 values ​​show X> 45 including very feasible categories, material experts obtained 37 which shows X> 36 categorical very feasible, language validation obtained a value of 33 indicating X> 33 which is in the very decent category. The practice of interactive powerpoint teaching materials is categorized as very practical in the learning process, this can be seen through trying One to one and Small groups by obtaining an X value greater than 42 with a very practical category. The results of the potential effects on the ability to understand student concepts in the learning process are seen as an average value of 39.31% of the learning outcomes in the medium category. For the high category, the average N-Gain calculation is 63. 60% includes a very good category. Keywords: Teaching materials, biodiversity, interactive powerpoints Abstrak. Penelitian ini bertujuan untuk menghasilkan bahan ajar berupa Powerpoint Interaktif materi kenakaragaman hayati. Metode penelitian inipengembangan Research and Development (R&D) dengan mengunakan model pengembangan Tessmer dengan tahapan Self Evaluation, Exspert Reviews, One to One, Small Group dan Field Test. Pengumpulan data berupa lembar angket, wawancara dan Kuisioner. Subjek dalam penelitian ini siswa kelas XI SMA Nurul Yaqin. Analisis hasil lembar validasi dan angket siswa pada penelitian ini adalah menggunakan teknik analisis kuantitatif dan kualitatif. Hasil penelitian validasi dikategorikan sangat layak, kelayakan bahan ajar Powerpoint Interaktif tergambar dari ahli media diperoleh nilai 46 yang menunjukan nilai X > 45 termasuk kategori sangat layak, ahli materi diperoleh 37 yang menunjukan X > 36 kategorik sangat layak, validasi bahasa diperoleh nilai 33 yang menunjukan X>33 yang termasuk kategori sangat layak.Kepraktisan bahan ajar powerpoint interaktif dikategorikan sangat praktis digunakan dalam proses pembelajaran, hal ini dapat dilihat melaluiui coba One to one dan Small group dengan memperoleh nilai X lebih besar dari pada nilai 42 dengan kategori sangat praktis. Hasil efek potensial terhadap kemampuan pemahaman konsep siswa dalam proses pembelajaran dilihat nilai rata-rata 39.31% hasil belajar dengan kategori sedang. Untuk kategori tinggi rata-rata perhitungan N-Gain 63. 60% termasuk kategori sangat baik. Kata Kunci: Bahan ajar, keanekaragaman hayati, powerpoint interaktif